Irish clientelism - a reappraisal - Komito, L (Economic & Social Studies, 1984)
Abstract: Studies of Irish politics have generally used a clientelist framework: voters in rural areas seem to obtain state benefits through a politician's interventions and, in return, become the politician's "clients". This article reports anthropological research on urban brokerage and clientelism carried out in Dublin from 1978 to 1981 which suggests that a more complex analytic model is required. Clientelism was relevant in the context of party politics, but voters who sought a broker's help did not necessarily become clients. Political brokerage did not guarantee individual voters' electoral support, and was largely used to enhance the politician's reputation in the community. It is thus useful to distinguish brokerage from clientelism; although the two are related, they are not interchangeable. In addition, the "currency" of brokerage was rarely politicians' influence over the actual allocation of state resources, but rather their information about bureaucratic procedures and their access to the bureaucrats themselves. There is no reason to presume that brokerage, based on such a monopoly over information and access, should necessarily decrease as Ireland becomes increasingly urban and industrial.
Keywords: Economics; Sociology